PENGARUH PENERAPAN MODEL PENCAPAIAN KONSEP (CONCEPT ATTAINMENT MODEL) TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI JAMUR KELAS X SMA NEGERI 2 INDERALAYA UTARA - Riska Agustina; Siti Huzaifah; Endang Dayat (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2016)
Abstract: This atudy aimed at finding out the effect of concept attainment model on students’ achievement of fungi. This research using pre experimental method with one group pre test post test design at class X.B SMA Negeri 2 Indralaya Utara (South Sumatera, Indonesia) academic year 2015/2016. The sample of the study was taken using simple random sampling. Data collected by the method of testing for learning achievement, by the method of observation for student activities and attitudes, and by the method of the questionnare for student responses of the implementation of the model of teaching. Activities, attitudes, and responses data are the supporting data in the study. The collected data was analyzed using t-test and descriptive statistic. Results showed there is significant effect of concept attainment model on students’ achievement (n-gain) 0,74 with categorized into high. The mean score of the students’ activities (visual, motoric, writing, and oral activities) is 88,40, categorized into active. The mean score of the students’ attitudes (honest, responsible, cooperation, tolerance, confidence, and discipline attitudes) is 97,91, categorized into excellent. The mean score of the students’ response is 88,17, categorized into good. Keywords : Concept Attainment Model, Learning Achievement, Activities, Attitude, Responses, and Fungi.